2020
DOI: 10.35371/aoem.2020.32.e7
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis of prevalence and medical expenses of cancer, cardio-cerebrovascular disease, psychiatric disease, and musculoskeletal disease in Korean firefighters

Abstract: Background: Firefighters are exposed to many dangerous working conditions. Many studies have identified the risk of disease for firefighters, but only a few studies have addressed the medical expenses of firefighters, which represents a concrete scale of disease. Our purpose in this study was to determine the medical expenditures of firefighters to assess the overall scale of disease in Korea. We focused on cancer, mental disorders, cardio-cerebrovascular disease, and musculoskeletal disease, the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Overall medical cost is higher in firefighters compared to the general population, and the cost for cerebro-cardiovascular disease is much higher. 28 Since inherent occupational risk cannot be totally under control in police officers and firefighters, the occupational risks mentioned in the present study and previous studies need to be comprehensively accepted. In this context, cerebro-cardiovascular events in those occupations may need to be rapidly compensated as disasters on duty, and this approach may be applicable for tertiary prevention.…”
Section: Discussionmentioning
confidence: 82%
“…Overall medical cost is higher in firefighters compared to the general population, and the cost for cerebro-cardiovascular disease is much higher. 28 Since inherent occupational risk cannot be totally under control in police officers and firefighters, the occupational risks mentioned in the present study and previous studies need to be comprehensively accepted. In this context, cerebro-cardiovascular events in those occupations may need to be rapidly compensated as disasters on duty, and this approach may be applicable for tertiary prevention.…”
Section: Discussionmentioning
confidence: 82%
“…Seven studies examining genitourinary disease were identified and reviewed [ 16 , 19 , 21 , 24 , 25 , 44 , 75 ]. Regarding the inter-comparison, most studies indicated a genitourinary disease SMR decrease between 0.38 and 0.54 in male firefighters as compared to the general population [ 16 , 21 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The models assessing male-factor infertility yielded the highest HR among full-time firefighters (HR, 1.46; 95% CI, 1.10 to 1.94) in the male. In Vitro Fertilization model and the male National Patient Register model (HR, 1.53; 95% CI, 1.18 to 1.98), compared to employees [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation